The Algorithmic Horizon: What is the Future of AI in Personalized Medicine? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The promise of personalized medicine—delivering the right treatment to the right patient at the right time—is rapidly transitioning from a theoretical ideal ...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation